Pengaruh Variasi Temperatur Heat Treatment Tempering dan Media Pendingin Terhadap Kekuatan Tarik Pada Baja AISI 4140 - Rakha Handika; Rahmat Romdloni (Universitas Muhammadiyah Metro, 2024)
AISI 4140 steel is a low-alloy steel widely applied in the manufacturing industry due to its good combination of strength, toughness, and wear resistance. To optimize its mechanical properties, proper heat treatment processes are necessary. Previous research has shown that variations in tempering temperature can affect the size and distribution of carbides, which in turn impacts the tensile strength of the steel. Additionally, the choice of cooling media influences the cooling rate and, consequently, the final microstructure and mechanical properties. In this study, the influence of heat treatment tempering temperature variation and cooling media on the tensile strength of AISI 4140 steel is relevant. This research employs an experimental method by varying the heat treatment tempering temperature and cooling media to compare the tensile strength of AISI 4140 steel under different heat treatment conditions. In this study, specimens were divided into two variation categories: specimens heated to 175°C and 250°C (heat treatment tempering). The tensile stress graph shows that the material tempered at 175°C in water achieved a high stress value of 2047.75 MPa, while the material tempered at 250°C in oil achieved 1793.51 MPa. For strain, the material tempered at 175°C in water achieved a high strain value of 13.28%, while the material tempered at 250°C in oil achieved a low strain value of 12.34%. From the results obtained, it can be concluded that for the tensile strength of AISI 4140 steel, the highest stress value was obtained for the material tempered at 175°C in water, and the lowest stress value was obtained for the material tempered at 250°C in oil. For strain, the highest value was obtained for the material tempered at 175°C in water, and the lowest value was obtained for the material tempered at 250°C in oil.